Humpback whale activity near Cap Lopez, Gabon - D. Walsh, Pete; Michael Fay, J.; Gulick, Steve; Phillipe Sounguet, Guy (J. Cetacean Res. Manage., 2000)
Two days of aerial transects were flown in mid-August 1998, just below the equator near Cap Lopez, Gabon. Two groups of humpback whales (Meagaptera novaeangliae) were sighted to the north of Cap Lopez and eighteen groups were sighted to the south. A large proportion of whales in the southern sector engaged in display behaviour. Similar observations were made during brief boat surveys on 14 August 1998 and 6-12 September 1999. Three surface-active groups were also observed, suggesting that humpback whales mate in the waters surrounding Cap Lopez. Three calves were observed during surveys. Historical whaling records and recent reports of whale sightings imply that humpback whale breeding grounds lie further north and west, in the Gulf of Guinea. Observations also suggest that humpback whales may feed at Cap Lopez and possibly at other points along the Gabonese coast. Common dolphins (Delphinus delphis) were abundant in the area and one other, unconfirmed, dolphin species was observed. Further research is needed to better establish the status of humpback whales and other cetaceans in the Gulf of Guinea.